Market-driven product ontologies: a conceptual framework for customer information integration in product innovation processes - Meersman, Davor (Curtin, 2009)
In this paper we introduce a market-driven product ontology for creating market orientation and customer focus in innovation and product development/marketing processes in the extended enterprise. We describe and evaluate the main building blocks and uses of the market-driven product ontology. We describe how the ontology can interact with innovation process system components such as case-based reasoners and TRIZ in order to decrease the knowledge acquisition bottleneck and leverage market learning capabilities. Finally, we discuss the suitability of the proposed solution for the issues at hand.